Airway Management During Anesthetic Induction of Secondary Laryngectomy for Recurrent Laryngeal Cancer: Three Cases of Report and Analysis - Zhang, Xuezheng; Cavus, Omer; Zhou, Ying; Dusitkasem, Sasima (Frontiers in Medicine, 2018)
Surgery for laryngeal cancer and the following recurrent tumor growth may further change the anatomy of the airway. Airway management during anesthesia induction is challenging for the patients undergoing secondary surgery due to recurrence of laryngeal cancer or its postoperative complication, but it has never been reported. In this report we described three cases of anesthetic induction which had different process of airway events. The first case was given intravenous general anesthetic for induction and experienced failed intubation, difficult mask ventilation and emergent tracheostomy, eventually were rescued successfully. The second case presented a fixed metastatic mass about 6 cm diameter upon the primary surgical scar of incision and preoperative apnea, underwent fibroscopy-guided conscious intubation and the process was uneventful. The third case had erythema and swelling under the mandible with erupted ulcer as well as neck immobility due to recurrent tumor. The anesthesiologist attempted fibroscopy-guided intubation via nasal passage with a tracheal tube in 2.8mm diameter but it was failed. Subsequently, tracheostomy was performed under bilateral superficial cervical plexus block and the dissected larynx by operation verified distorted structure of glottis with S-shaped stenosis. This report concludes that, during the anesthetic induction for this special type of surgery, detailed and comprehensive evaluation of the airway, and routine fibroscopic examination are especially important.